Open and Minimal Approaches to Pancreatic Adenocarcinoma. (27th May 2020) - Bhogal, Ricky H.; Pericleous, Stephanos; Khan, Aamir Z.
Abstract : Surgical options and approaches to pancreatic cancer are changing in the current era. Neoadjuvant treatment strategies for pancreatic cancer combined with the increased use of minimal access surgical techniques mean that the modern pancreatic surgeon requires mastering a number of surgical approaches with to optimally manage patients. Whilst traditional open surgery remains the most frequent approach for surgery, the specific steps during surgery may need to be modified in light of the aforementioned neoadjuvant treatments. Robotic and laparoscopic approaches to pancreatic resection are feasible, but these surgical methods remain in their infancy. In this review article, we summarise the current surgical approaches to pancreatic cancer and how these are adapted to the minimal access setting with discussion of the patient outcome data.